Some Almost Generalized (ψ,ϕ)-Contractions in G-Metric Spaces - Hassen Aydi; Sana Hadj Amor; Erdal Karapinar (Abstract and Applied Analysis)
In this paper, we introduce some almost generalized (ψ,ϕ)-contractions in the setting of G-metric spaces. We prove some fixed points results for such contractions. The presented theorems improve and extend some known results in the literature. An example is also presented.